Microbial Transformation of neo-Clerodane Diterpenoid, Scutebarbatine F, by Streptomyces sp. CPCC 205437 - Zhang, Dewu; Tao, Xiaoyu; Gu, Guowei; Wang, Yujia; Zhao, Wenxia; Zhao, Wuli; Ren, Yan; Dai, Shengjun; Yu, Liyan (Frontiers in Microbiology, 2021)
Biotransformation of the neo-clerodane diterpene, scutebarbatine F (1), by Streptomyces sp. CPCC 205437 was investigated for the first time, which led to the isolation of nine new metabolites, scutebarbatine F1–F9 (2–10). Their structures were determined by extensive high-resolution electrospray ionization mass spectrometry (HRESIMS) and NMR data analyses. The reactions that occurred included hydroxylation, acetylation, and deacetylation. Compounds 2–4 and 8–10 possess 18-OAc fragment, which were the first examples of 13-spiro neo-clerodanes with 18-OAc group. Compounds 7–10 were the first report of 13-spiro neo-clerodanes with 2-OH. Compounds 1–10 were biologically evaluated for the cytotoxic, antiviral, and antibacterial activities. Compounds 5, 7, and 9 exhibited cytotoxic activities against H460 cancer cell line with inhibitory ratios of 46.0, 42.2, and 51.1%, respectively, at 0.3 μM. Compound 5 displayed a significant anti-influenza A virus activity with inhibitory ratio of 54.8% at 20 μM, close to the positive control, ribavirin.